Myeloid-Derived Suppressor Cells: A Multifaceted Accomplice in Tumor Progression - Cheng, Jia-Nan; Yuan, Yi-Xiao; Zhu, Bo; Jia, Qingzhu (Frontiers in Cell and Developmental Biology, 2021)
Myeloid-derived suppressor cells (MDSCs) have a key role in tumor progression. Their underlying mechanisms are complex and diverse, including immunosuppressive functions (inhibition of cytotoxic T cells and recruitment of regulatory T cells) and non-immunological functions (mediating stemness and promoting angiogenesis). Moreover, MDSCs mediate acquired resistance to immunotherapy and predict poor prognoses for various tumors. Therefore, many clinical trials have attempted to utilize MDSCs for cancer treatment. This review summarizes the definite mechanisms of MDSCs in tumor progression and targeting strategies to provide new insights regarding their clinical applications.